Zoonotic tick-borne pathogens in ticks from vegetation and alpine ibex (Capra ibex) in the maritime alps, Italy - Menzano, Arianna; Tizzani, Paolo; Farber, Marisa Diana; Garcia-Vozmediano, Aitor; Martinelli, Laura; Rossi, Luca; Tomassone, Laura (MDPI, 2024)
In the Maritime Alps (northwestern Italy), we collected ticks from vegetation and Alpine ibex (Capra ibex). Ixodes ricinus was the most abundant species in the study area, questing up to 1824 m a.s.l. and infesting 28 out of 72 ibexes. Haemaphysalis punctata, H. sulcata and Dermacentor marginatus were also collected. The abundance of questing ticks significantly decreased with altitude, with beechwoods being the preferred habitat. By PCR, we identified Borrelia burgdorferi s.l. in questing I. ricinus (28.3%; 95%CI: 19.4–38.6) but not in specimens collected from animals. Rickettsia spp. infected both questing (20.6%; 95%CI: 12.9–30.3) and on-host (30.2%; 95%CI: 21.2–40.4) I. ricinus. Anaplasma phagocytophilum was detected in 4.3% (95%CI: 1.2–10.8) of questing I. ricinus and in 45.3% (95%CI: 34.6–56.4) of I. ricinus collected from ibex. Female I. ricinus collected on animals were significantly more infected with A. phagocytophilum than females collected from vegetation (OR = 11.7; 95%CI: 3.8–48.1). By amplifying and sequencing a fragment of the groEL gene, we identified 13 groEL haplotypes, clustering with ecotypes I and II; ecotype I, prevalent in our sample, is considered zoonotic. Our study demonstrates the presence of different tick-borne zoonotic agents in the study area, encompassing a wide altitudinal range, as confirmed by the ticks found on ibex, a typical mountain-dwelling mammal. The results also confirm the altitudinal range expansion of ticks and associated pathogens in the Alps and suggest that Alpine ibex may act as a reservoir for A. phagocytophilum, as do other wild ungulate species.